A novel stability-enhanced lithium-oxygen battery with cellulose-based composite polymer gel as the electrolyte. (10th September 2015) - Leng, Limin; Zeng, Xiaoyuan; Chen, Peng; Shu, Ting; Song, Huiyu; Fu, Zhiyong; Wang, Haishui; Liao, Shijun
Highlights: A novel cellulose-based composite polymer gel electrolyte (PGE) membrane is prepared. PGE exhibits excellent ionic conductivity and electrochemical stability. PEG reduces the penetration of oxygen to lithium anode and electrolyte loss. Non-aqueous Li/O2 battery employing PGE membrane displays good cyclic stability. Abstract: A novel lithium-oxygen (Li-O2 ) battery with a polymer gel electrolyte (PGE) membrane is successfully prepared. The membrane is a blend of cellulose acetate (CA) and poly(vinylidene fluoride- co -hexafluoropropylene) (P(VDF-HFP)) and is fabricated using a solution casting technique followed by impregnation with lithium bis(trifluoromethane sulfonimide) (LiTFSI) solution. We demonstrate that the PGE membrane has good electrolyte uptake and shows high ionic conductivity as well as excellent thermal and electrochemical stability. A Li-O2 battery containing our PGE as the electrolyte and separator exhibits good rate capability and enhanced cycling capacity retention compared to a battery using commercial liquid electrolyte and a polyethylene (PE) separator under the same conditions. We attribute this enhanced performance to the PGE, which maybe restrain the diffusion of oxygen from the air cathode to the Li metal anode. This study may prove valuable for resolving the problem of poor cycling stability in Li-O2 batteries caused by oxygen diffusion from cathode to anode.